Mycosis Fungoides: A Retrospective Study of 44 Swedish Cases - Eklund, Yvonne (2016)
Mycosis fungoides (MF) is a primary cutaneous T-cell lymphoma with slow disease progression. There is a lack of descriptive data from Sweden concerning patients with this diagnosis. This study extracted data on patients admitted to the dermatology department at Lund University Hospital, Sweden from 1996 to 2010. Forty-four patients with clinically and histopathologically verified MF were identified during the period, with a mean follow-up time of 5.6 years. Median age at initial diagnosis was 64 years. In several cases other skin diseases preceded MF onset, such as non-specific dermatitis (32%) and parapsoriasis (30%). The majority of patients (86%, n = 38) had limited-stage (IA–IB) disease at the time of diagnosis. Overall response rate to psoralen plus ultraviolet A (PUVA) treatment was 81%. In adnexal MF, a trend to higher rate of progression to an advanced stage was observed when compared with non-adnexal disease (40% and 21%, respectively). Increased levels of soluble interleukin-2 (IL-2) receptor correlated with disease stage, being elevated in advanced stages or adnexal disease, but almost never elevated in early non-adnexal limited-stage disease. Overall mortality was 25%, but only 11% could be verified as caused by MF.